Hyperbranched polyester improves the dispersion of SiO2 for enhancing the mechanical properties of DLP 3D printing polyurethane acrylate - Zhao, Xiaoliang; Jiao, Hua; Yao, Yijun; Du, Bin; Zhao, Kang (Polymer engineering and science, 2025)
Herein, we prepared the high‐strength polyurethane acrylate (PUA) composites by introducing the γ‐methacryloxypropyltrimethoxysilane (γ‐MPS)‐modified SiO2 (γ‐MPS‐SiO2) and hyperbranched unsaturated polyester (U102) into PUA utilizing digital light processing 3D printing technology. Fourier transform infrared, 1H NMR, and gel permeation chromatography provided evidence for the preparation of PUA and γ‐MPS‐SiO2. And U102 could improve the dispersion of γ‐MPS‐SiO2 particles in PUA, which is conducive to improving the tensile strength, bending strength, and thermal stability of PUA composites. Compared with γ‐MPS‐SiO2/PUA, γ‐MPS‐SiO2/U102/PUA composites with tensile strength of 32.73 MPa and bending strength of 62.48 MPa can be obtained when the content of U102 is 10 wt%. The thermal stability and mechanical properties of PUA composites increased with the increase of γ‐MPS‐SiO2 content. When the content of γ‐MPS‐SiO2 particles is 20 wt%, T5%, T50%, and the residue at 650°C are increased by 36.81%, 2.31%, and 122.17%, respectively. The tensile and bending strengths were increased by 103.67% and 125.92%, respectively. This work provides a new way to improve the dispersibility of inorganic nanoparticles in polymers and the mechanical properties of photocurable 3D printing resin products. Highlights A high‐performance photocurable polyurethane acrylate has been synthesized. The hyperbranched unsaturated polyester has an excellent dispersing effect on SiO2. The mechanical properties of polyurethane acrylate composites were synergistically improved by the hyperbranched unsaturated polymer and SiO2 particles. Preparation principle of γ‐MPS‐SiO2/U102/PUA composites and their mechanical properties.